The Effectiveness of Whispering Game to Students’ Vocabulary Mastery - Sari Delima Sihaloho; Juwita Boneka Sinaga; Sulastri Manurung (ANGLO-SAXON: Jurnal Ilmiah Program Studi Pendidikan Bahasa Inggris, 2017)
In this research, there are many problems in learning process in the class. The problems are lack of vocabulary, and method of teaching vocabulary used. This research has purpose to students’ vocabulary mastery by using whispering game at the SMP Kartini II Batam academic Year 2015/2016. This research is quantitative research. The researcher used total sampling. The experimental class was taught using whispering game, whereas the control class was taught using lecturing method. In this research, the researcher gave 20 of questions in multiple choices form. The result of analysis can be concluded that there was significant effect. It was showed     (3,01 2,01) so  was rejected and  was accepted. The result of analysis can be concluded that the use of whispering game at SMP Kartini II Batam in academic Year 2015/2016  gave significant effect in the students’ activity in learning process than the use of close procedure. Keyword : whispering game, vocabulary mastery